2015
DOI: 10.1080/13607863.2015.1047321
|View full text |Cite
|
Sign up to set email alerts
|

The care needs of older patients with bipolar disorder

Abstract: Older bipolar patients report fewer needs and unmet needs compared to older patients with depression, schizophrenia, and dementia. A plausible explanation is that older bipolar patients had higher Global Assessment of Functioning scores, were better socially integrated, and had fewer actual mood symptoms, all of which correlated with the number of needs in this study. The results emphasize the necessity to assess the needs of bipolar patients with special attention to social functioning, as it is suggested tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 31 publications
3
17
0
Order By: Relevance
“…And this is striking because in an ambulatory health care setting one should expect that the ambulatory healthcare professionals also address the needs in the social domain. This is also discussed in another study on bipolar patients in a similar setting (Dautzenberg et al, 2016). We agree with Dautzenberg et al (2016) that it is probably a demarcation problem in which ambulatory health care professionals do not regard these problems within their scope of attention and address care needs in the social domain to other health care facilities (e.g.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…And this is striking because in an ambulatory health care setting one should expect that the ambulatory healthcare professionals also address the needs in the social domain. This is also discussed in another study on bipolar patients in a similar setting (Dautzenberg et al, 2016). We agree with Dautzenberg et al (2016) that it is probably a demarcation problem in which ambulatory health care professionals do not regard these problems within their scope of attention and address care needs in the social domain to other health care facilities (e.g.…”
Section: Discussionsupporting
confidence: 67%
“…From the results of this study, we have some concerns about the provided care in the social domain. From other studies (Dautzenberg et al, 2016;Houtjes et al, 2010) we know that most of the unmet needs are found in the social domain. The results of this study show that in about 30% of the unmet needs remain undetected (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Dautzenberg et al () conducted a needs assessment among patients age 60 years and older who were receiving services for BD. They found that, overall, needs were low; however, the most common unmet individual needs included household skills, physical health, medication, and psychological distress.…”
Section: A Clinical Picturementioning
confidence: 99%
“…International studies project that the population of older people with severe mental illness (SMI) will increase in the coming decades (Clifton, Marples, and Clarke 2013; NBHW (National Board of Health and Welfare) 2013). This implies a challenge for the provision of health and welfare services in many countries (OECD 2011), due the deficient understanding of the living situation and care needs of older people with SMI (Dautzenberg et al 2016;Warner and Jenkinson 2013).…”
Section: Introductionmentioning
confidence: 99%